If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9 = 3(-8 + x) 9 = (-8 * 3 + x * 3) 9 = (-24 + 3x) Solving 9 = -24 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 9 + -3x = -24 + 3x + -3x Combine like terms: 3x + -3x = 0 9 + -3x = -24 + 0 9 + -3x = -24 Add '-9' to each side of the equation. 9 + -9 + -3x = -24 + -9 Combine like terms: 9 + -9 = 0 0 + -3x = -24 + -9 -3x = -24 + -9 Combine like terms: -24 + -9 = -33 -3x = -33 Divide each side by '-3'. x = 11 Simplifying x = 11
| -1+2p=41 | | 16+6a=4(a+2)+a | | (1/2)x=64 | | -4+11x=-7(-4x-11)+10x | | 8m-4m=17+9m+3-7m | | x+3+6=-23+5x | | 3(-6-3n)+5n=-2(-8n-1) | | -6x-7x=3x-4x | | (3x-9z)2= | | -6x-7x=3x-4c | | -4+3b+b=-3+3b | | -t^2+16t+40=0 | | (3+2a)(2a-3)= | | -12-3n=6(12n-2) | | 17+11v=8+4(-7+12v) | | -3+4r=-23-r | | 0=16t-t^2+40 | | 3x-12x=10-4x | | 4=100y^2 | | -3(1+n)+7n=5(2+n) | | 12+7-6x-7=4-7x | | 0=16-t^2+40 | | 5x-5x-1=2x+5 | | 33-3a=6(a-5) | | 8(7r-1)=-8+2r | | 8(-8+4x)=-36+4x | | 8(-8+4x)=36+4x | | 2(4-4n)=-6+6n | | 9x+13=11x | | 17x+108=y | | 8w-11=69 | | 16=-16x^2+36 |